2005
DOI: 10.1200/jco.2005.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Index for Adult Patients With Acute Myeloid Leukemia in First Relapse

Abstract: The prognostic index estimates the outcome of AML patients in first relapse using four commonly applied clinical parameters and might identify patients who are candidates for salvage and investigational therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
383
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 464 publications
(405 citation statements)
references
References 23 publications
15
383
5
2
Order By: Relevance
“…A successful outcome after salvage therapy depends on duration of first CR, cytogenetics at diagnosis and previous history of ASCT [8][9][25][26][27]. Although the difference was not statistically significant, likely due to the small sample size, we observed that patients younger than 60 years and those with CR1 duration ≥12 months had a higher response rate.…”
Section: Bleedingcontrasting
confidence: 46%
“…A successful outcome after salvage therapy depends on duration of first CR, cytogenetics at diagnosis and previous history of ASCT [8][9][25][26][27]. Although the difference was not statistically significant, likely due to the small sample size, we observed that patients younger than 60 years and those with CR1 duration ≥12 months had a higher response rate.…”
Section: Bleedingcontrasting
confidence: 46%
“…Outcome of allografts beyond first remission, however, is inferior to that in first-remission patients, owing to an increase in both treatmentrelated mortality (25%-35%) and relapse (40%-45%). Breems et al reported a prognostic index for adult patients with relapsed AML based on a cohort of 667 AML patients in first relapse (115). Four relevant parameters significantly predicted for outcome, including length of relapse free interval, age at relapse, cytogenetics at diagnosis, and whether or not patients had received a previous transplantation.…”
Section: Transplantation In Second Remissionmentioning
confidence: 99%
“…Older individuals with myeloid diseases also have high risk cytogenetic phenotypes and increased multidrug resistance gene expression [1][2][3]; hence they are less likely cured with chemotherapy alone. Allogeneic hematopoietic stem cell transplantation (HSCT) is potentially curative with a reported disease-free survival (DFS) of 30-50% [4][5][6][7][8][9]. In MDS, HSCT is the only therapy known to improve survival [10].…”
Section: Introductionmentioning
confidence: 99%